New design of three-qubit system with three transmons and a single fixed-frequency resonator coupler - Jeongsoo Kang; Chanpyo Kim; Younghun Kim; Younghun Kwon (Scientific Reports)
Abstract The transmon, which has a short gate time and remarkable scalability, is the most commonly utilized superconducting qubit, based on the Cooper pair box as a qubit or coupler in superconducting quantum computers. Lattice and heavy-hexagon structures are well-known large-scale configurations for transmon-based quantum computers that classical computers cannot simulate. These structures share a common feature: a resonator coupler that connects two transmon qubits. Although significant progress has been made in implementing quantum error correction and quantum computing using quantum error mitigation, fault-tolerant quantum computing remains unachieved due to the inherent vulnerability of these structures. This raises the question of whether the transmon-resonator-transmon structure is the best option for constructing a transmon-based quantum computer. To address this, we demonstrate that the average fidelity of CNOT gates can exceed 0.98 in a structure where a resonator coupler mediates the coupling of three transmon qubits. This result suggests that our novel structure could be a key method for increasing the number of connections among qubits while preserving gate performance in a transmon-based quantum computer.